Neonatal nurses' perceptions of using live streaming video cameras to view infants in a regional NICU. Issue 4 (August 2020) - Kilcullen, Meegan Lesley; Kandasamy, Yogavijayan; Evans, Michelle; Kanagasignam, Yogesan; Atkinson, Ian; van der Valk, Steven; Vignarajan, Janardhan; Baxter, Michelle
Abstract: Tertiary hospital services have introduced live streaming video cameras into Neonatal units with the aim of reducing distress and enhancing bonding and attachment between infants and parents during hospitalisation. However, there is a paucity of research exploring the impact of using live streaming video cameras in the neonatal unit. The aim of this study was to describe staff perceptions of using a live streaming video camera in a neonatal context. Quantitative and qualitative data were collected via an online questionnaire. While staff reported benefits for parents, concerns regarding increased workload and difficulties in using the technology were also reported. For this technology to be implemented as standard care, and to ensure nurses confidence in using it, it will be important to address these concerns. Working in collaboration with nurses who have daily and ongoing experience with the cameras in clinical practice is key to finding effective solutions for implementing live web streaming cameras into standard care.